THE OPERATIONAL RELIABILITY OF THE CONTACT CONNECTIONS OF ELECTRO-CONTACTORS AND CONTACTORS ECG-8G OF AC LOCOMOTIVES - Teterko, O. A.; Babjak, M. A.; Kostin, M. O. (Science and Transport Progress, 2007)
The types of refusals which arise up in the process of exploitation of electropneumatic contactors PC-96-101 are considered. Measuring of contact resistance and heating temperature of contact connections of alternating current electric locomotives are resulted. The features of electric erosion of contacts from different composition materials after the models tests are considered.